ANALYSIS OF CRIMINAL RESPONSIBILITY OF PERPETRATORS OF CRIMINAL ACT OF ASSAULT CAUSING DEATH FROM THE PERSPECTIVE OF VICTIM PROTECTION (Decision Study Number: 185/Pid.B/2024/PN Smg) - Alifka, Muhammad Fauzi Nur Alifka; Soponyono, Eko (Jurnal Hukum Khaira Ummah, 2024)
The act of abuse is one of the phenomena that is difficult to eliminate in community life, which often occurs such as beatings and physical violence often resulting in injuries to the victim's body or limbs, not infrequently making the victim physically disabled for life, or even resulting in death. Even to the point of causing the victim to die, the demands of punishment for the perpetrator of the crime must really provide a sense of justice for the victim, the victim's family and even the perpetrator himself in order to provide a lesson and a deterrent effect. As a responsibility to the perpetrator of the crime in connection with the law enforcement process given to the guilty person lies in what crime he committed. The approach method used is normative juridical, namely a library legal research conducted by examining library materials or secondary data alone using the deductive thinking method. The writing specifications use descriptive analysis, the sources and types of data used are secondary data. The method of data collection by collecting data using the secondary data collection method. The problem is analyzed with the theory of criminal responsibility and the theory of justice. Acts of abuse committed by someone either intentionally or unintentionally must be ascertained first to determine the sanctions that will be punished for that person. The existence of the perpetrator's abuse is actually intended for the pain of a person, not for the purpose of his death, meaning the perpetrator's intention. Human rights are basic rights that are inherently inherent in humans, are universal and direct. This also includes the rights that must be obtained by victims of abuse. In a legal event, of course, it starts from a legal act, from a legal act a legal bond or relationship will arise, so it can be interpreted that the legal consequences can arise from legal acts and/or legal relationships. Victims of crime generally face a criminal justice system that is often busy with police and prosecutorial affairs rather than directly dealing with the perpetrator. Worse still, the focus of attention in the justice and criminal justice system is not on the victim who clearly suffers the most losses, but rather more on the perpetrator of the crime.